Protection of Socio-economic Rights under the ECHR - Milašiūtė, Vygantė (Teisė, 2020)
The article examines to what extent and how the protection of socio-economic rights can be and is actually effected under the ECHR. This is done taking into account the fact that the protection of such rights is not a major objective of the ECHR but, in view of the indivisibility of human rights, the realisation of some socio-economic rights is necessary for the realisation of the ECHR rights.